2020
DOI: 10.1111/jphs.12376
|View full text |Cite
|
Sign up to set email alerts
|

Investigating prescribing errors in the emergency department of a large governmental hospital in Jordan

Abstract: Background Although prescribing errors (PEs) are the most common type of medication errors and cause morbidity and mortality, they have been rarely studied. Objective The study aimed to investigate PEs incidence, types, severity, causes, predictors, pharmacists' interventions accepted by doctors and computer‐related errors. Setting This study was conducted in the emergency department of the largest governmental hospital in Jordan. Method This was a retrospective observational 4‐week study. A validated definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…These efforts might be the reason for the general controlled situation in the country. Medication safety-based research is rare in the Arabic region; most of the previous studies were conducted in hospital settings to document prescribing safety in the emergency departments 41 or the role of clinical pharmacists in reducing prescription-related errors. 42 This study had many limitations: (1) each community pharmacy operates nearly different system for medication dispensing, thus bias could be induced due to the variation, (2) due to lack of time and avoiding close personal contact with the staff and the patients, the main outcomes of this study may be underestimated, (3) the rate of acceptance for pharmacist interventions was beyond the scope of the study due to practical reasons, (4) we were unable to determine the impact of missing information on the accuracy of our findings, and (5) outcomes such as factors associated with error severity, causes, cost analysis, and channels of medicine delivery were unexamined in this study.…”
Section: Pharmacist Counselingmentioning
confidence: 99%
“…These efforts might be the reason for the general controlled situation in the country. Medication safety-based research is rare in the Arabic region; most of the previous studies were conducted in hospital settings to document prescribing safety in the emergency departments 41 or the role of clinical pharmacists in reducing prescription-related errors. 42 This study had many limitations: (1) each community pharmacy operates nearly different system for medication dispensing, thus bias could be induced due to the variation, (2) due to lack of time and avoiding close personal contact with the staff and the patients, the main outcomes of this study may be underestimated, (3) the rate of acceptance for pharmacist interventions was beyond the scope of the study due to practical reasons, (4) we were unable to determine the impact of missing information on the accuracy of our findings, and (5) outcomes such as factors associated with error severity, causes, cost analysis, and channels of medicine delivery were unexamined in this study.…”
Section: Pharmacist Counselingmentioning
confidence: 99%
“…In Jordan, no studies have investigated MEs in general, though some studies have investigated medication errors in particular. 8–12 In a study conducted in Jordan, the rate of medication errors using incident reports was 42%. 13 Another study reported a medication error rate of 35% (ie 36.4% in ICUs and 33.8% in wards).…”
Section: Introductionmentioning
confidence: 99%
“…17 Among the developing countries, medication errors, particularly dispensing errors are common. 7,18,19 Dispensing of antibiotics without prescriptions and based on inappropriate reasons has been documented in Mozambique. 20 In Ghana, patients were satisfied with the dispensing process in community pharmacies.…”
Section: -16mentioning
confidence: 99%